Resiliensi dan Kehidupan Sehari-hari dalam Keluarga Banyumasan: Iman, Humor, dan Gotong Royong - Muhammad Fuad Zain; Syifaun Nada; M. Yudha Ditta Wiratama (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study explores family resilience in the Banyumasan community through a socio-cultural perspective, drawing on Walsh’s Family Resilience Framework, the Double ABC-X Model, and Bronfenbrenner’s ecological systems theory. Employing a qualitative approach with interviews, participant observation, and documentation, data were collected from twelve households across peri-urban, highland, and lowland contexts, alongside community leaders, religious figures, and women’s group activists. The findings show that resilience is anchored in gotong royong (mutual cooperation), egalitarian interaction, and the cultural symbolism of the Ngapak dialect. Belief systems shaped by Islamic faith and Banyumasan pragmatism facilitate meaning-making, while kinship-based networks and neighbourly solidarity sustain economic and social survival. Direct, humorous communication reduces ambiguity and enhances collective problem-solving. Livelihood diversification strengthens economic security, whereas migration simultaneously improves material welfare and strains relational and educational dimensions. By linking these dynamics to national policy indicators, the study demonstrates that Banyumasan families exemplify resilience processes that are both culturally distinctive and policy-relevant, offering insights for culturally grounded and migration-sensitive interventions.